2022
DOI: 10.3389/fendo.2022.1032914
|View full text |Cite
|
Sign up to set email alerts
|

Implicating factors in the increase in cases of central precocious puberty (CPP) during the COVID-19 pandemic: Experience of a tertiary centre of pediatric endocrinology and review of the literature

Abstract: Sexual development is a complex mechanism activated by the hypothalamic-pituitary-gonadal axis. Over the last one hundred years there has been a decline in the age at puberty onset in industrialised countries. Some Italian studies showed an increase in diagnoses of Central Precocious Puberty (CPP) during the COVID-19 pandemic. It is thus supposed that in this period there was an increased impact of factors that can influence pubertal development. Our retrospective monocentric study aimed to confirm the existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Recently, several centers of pediatric endocrinology worldwide, including ours, have observed a further significant increase in the number of girls presenting with precocious or early puberty since mid-2020 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). During this period, corresponding to the first wave of COVID-19 pandemic, the Italian government imposed a strict lockdown across the country, in order to reduce the transmission rate and to avoid hospital bed saturation.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, several centers of pediatric endocrinology worldwide, including ours, have observed a further significant increase in the number of girls presenting with precocious or early puberty since mid-2020 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). During this period, corresponding to the first wave of COVID-19 pandemic, the Italian government imposed a strict lockdown across the country, in order to reduce the transmission rate and to avoid hospital bed saturation.…”
Section: Introductionmentioning
confidence: 89%
“…This is in accordance with our finding that the normal weight and underweight patients with diabetes showed a similar secular trend to that in the overweight patients. The "gold standard" for the biochemi- Several studies 35,36 have recently reported that central precocious puberty occurred about three times more frequently during the COVID-19 pandemic in various countries. In particular, psychosocial stress during the lockdowns and changed lifestyle have been associated with this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 35,36 have recently reported that central precocious puberty occurred about three times more frequently during the COVID‐19 pandemic in various countries. In particular, psychosocial stress during the lockdowns and changed lifestyle have been associated with this observation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Over 100 countries imposed variable lockdown measures either at local or national level following COVID-19, depending on the extent of spread of infection. Many countries imposed restrictions on flights from China, movement, and social contact, as well as visitors from high-risk areas were required to be quarantined (Coronavirus, 2020).Individuals, particularly children, were highly likely to spend more time at home due to the lockdown mandated by the governments of several countries, including Pakistan, Brazil, India, Turkey and China affecting their daily routine significantly (Ali et al, 2022;Barberi et al, 2022;Prosperi & Chiarelli, 2022). Lifestyle changes, such as dietary habits and sleep schedules, can have a substantial impact on a child's sexual development, including the initiation of puberty (Li et al, 2022).…”
mentioning
confidence: 99%
“…Individuals, particularly children, were highly likely to spend more time at home due to the lockdown mandated by the governments of several countries, including Pakistan, Brazil, India, Turkey and China affecting their daily routine significantly (Ali et al, 2022;Barberi et al, 2022;Prosperi & Chiarelli, 2022). Lifestyle changes, such as dietary habits and sleep schedules, can have a substantial impact on a child's sexual development, including the initiation of puberty (Li et al, 2022).…”
mentioning
confidence: 99%